PENENTUAN RUTE DISTRIBUSI SPARE PART KENDARAAN BERMOTOR DALAM MEMINIMALKAN BIAYA TRANSPORTASI: Array (Universitas Harapan Medan, 2019)
The goal of the distribution system is to deliver the product promptly and generate the minimum cost. The development of distribution system is very important because it can support the growth and development of the company. This study aims to get the route of delivery of the most appropriate and optimal products and get transportation cost savings. IPK is a company engaged in the production of automotive. The problems faced by IPK is the absence of good product distribution planning and scheduling distribution process is considered not maximal. This is due to the number of routes are too many, the distance is too far delivery, the limited means of conveyance and utilization of transport space less than the maximum and the high cost of transportation. To solve the problem is Saving Matrix method which is used to determine product distribution route to customer based on the capacity of conveyance. From the result with Saving Matrix method and algorithm method obtained 49 best route. The distance to be taken is as far as 6,010 kilometers with transportation cost of Rp. 46,630,527. The resulting distance saving is 22% (1,690.9 km), while the transportation cost savings that occur is 38% or Rp. 28,494,021.